2012
DOI: 10.5120/5636-8022
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Class of a Mentally Disabled Patient to Check the Level of Mental Retardation by using Feed Forward Back Propagation Neural Network

Abstract: Mental disorders have a large impact on individuals, families, and communities, and are one of the main causes worldwide of disability and distress. Correct diagnosis of mental disorders is essential in clinical practice, pharmacological research, and successful treatment. Patients with mental retardation often have multiple and sometimes complicated medical problems. In this paper we have proposed a feed forward back propagation neural network to classify the level of mental retardation by using Matlab softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…Stigma yang didapatkan anak tunagrahita sebagai orang bodoh serta memiliki kemampuan pemahaman intelektual yang rendah. Bahkan deskriminasi yang dialami anak tunagrahita terlihat di negara Asia dimana ana tunagrahita masih mendapatkan perlakuan yang kurang manusiawi, (Gupta& Mathur, 2012).…”
Section: Pendahuluanunclassified
“…Stigma yang didapatkan anak tunagrahita sebagai orang bodoh serta memiliki kemampuan pemahaman intelektual yang rendah. Bahkan deskriminasi yang dialami anak tunagrahita terlihat di negara Asia dimana ana tunagrahita masih mendapatkan perlakuan yang kurang manusiawi, (Gupta& Mathur, 2012).…”
Section: Pendahuluanunclassified
“…Kecacatan yang dialami oleh siswa tunagrahita menyebabkan mereka mengalami diskriminasi dalam masyarakat, hal ini terlihat di beberapa negara di Asia dimana penyandang disabilitas termasuk siswa tunagrahita masih mendapatkan perlakuan yang tidak manusiawi (Gupta & Mathur, 2012).…”
Section: Pendahuluanunclassified
“…For instance, a person might be understandable to someone which would present him less retard however the same person may not be understandable to other person, so he will be considered highly retard by the other person. Surveys have given an estimate that 85 % of mental [2] patients are least severely retarded, or can be categorized into mild group. Carving and understanding the facts and truth of the mentally impairment people, it is found that population categorized under mild MR have an IQ scores amid fifty to seventy-five.…”
Section: Mild and Moderate Mental Retardationmentioning
confidence: 99%